Cardiotonic Steroids as Modulators of Neuroinflammation - Orellana, Ana Maria; Kinoshita, Paula Fernanda; Leite, Jacqueline Alves; Kawamoto, Elisa Mitiko; Scavone, Cristoforo (Frontiers in Endocrinology, 2016)
Cardiotonic steroids (CTS) are a class of specific ligands of the Na+,K+- ATPase (NKA). NKA is a P-type ATPase that is ubiquitously expressed and although well known to be responsible for the maintenance of the cell electrochemical gradient through active transport, NKA can also act as a signal transducer in the presence of CTS. Inflammation, in addition to importantly driving organism defense and survival mechanisms, can also modulate NKA activity and memory formation, as well as being relevant to many chronic illnesses, neurodegenerative diseases and mood disorders. The aim of the current review is to highlight the recent advances as to the role of CTS and NKA in inflammatory process, with a particular focus in the central nervous system.